REBUILD: Regenerative Buildings and Construction systems for a Circular Economy. (January 2019) - Ajayabi, Atta; Chen, Han-Mei; Zhou, Kan; Hopkinson, Peter; Wang, Yong; Lam, Dennis
Abstract: Buildings and construction have been identified as having one of the greatest potential for value creation and capture from the application of circular economy principles. To achieve this requires a fundamental transformation in the recovery, remanufacture and re-use of end of service life structural products such as steel, bricks, concrete which make up the largest proportion of materials. At the same time these products must be re-used in new buildings and infrastructure designed for subsequent deconstruction and disassembly. REBUILD is a 3 year way UK research project to address this challenge. Initial findings on quantifying the material intensity of buildings (stock and flow assessment) are presented based on one of our case study cities. Results from new techniques to separate and reclaim bricks from cement mortar shows technical feasibility and ability to retain structural performance. Details on the next stage of scaling this work and techniques for separating and reclaiming steel and concrete are briefly described. Subsequent stage of life cycle assessment, value stream mapping and creating products for new forms of circular building and construction systems are also described. The paper concludes that whilst there are considerable challenges in reclaiming structural products that re-designed circular building and construction system could transform the value of end of service life buildings and the offers new opportunities for circular innovation and the circulation of materials and products at their highest value for the longest period.